Composing for voice exploring voice, language and music - Barker, Paul 1956-; Huesca, Maria (Routledge voice studies series, 2018)
"Composing for Voice: Exploring Voice, Language and Music, Second Edition, elucidates how language and music function together from the perspectives of composers, singers and actors, providing an understanding of the complex functions of the voice pedagogically, musicologically and dramatically. Composing for Voice examines the voice across a wide range of musical genres (including pop, jazz, folk, classical, opera and the musical) and explores the fusion of language and music that is unique to song. This second edition is enlarged to attract a wider readership amongst all music and theatre professionals and educators, whilst also engaging an international audience with the introduction of new co-author Maria Huesca. New to the second edition:A review of the history of singingAn overview of the development of melismaA chapter designed to help performers understand each other, as singers and actors often receive disparate educationsCase studies and qualitative research around song, lyric and meaningA discussion of the synthetic voiceAn introduction to the concept of embodied compositionInterviews with composers and singersSummaries of various vocal styles, including bel canto, the lyric voice, the belt voice, the rap voice, the dramatic voice, the virtuoso voice, the folk voice, the crooner, the live voice and the actor's voiceA website with many of the links and performances of music discussed, as well as related workshops and seminars: www.composingforvoice.comComposing for Voice: Exploring Voice, Language and Music, Second Edition, articulates possibilities for the practical exploration of language, music and voice by composers, singers and actors."--Provided by publisher